EstGeoMag: integrando soluções de hardware, software e internet das coisas na medição de grandezas geomagnéticas - Oliveira, Fábio Franco de (2017)
The magnetic field around the planet Earth is generated by the effect of its core, composed of metal in liquid form with temperatures in the order of 6000 ∘C. This field, which extends for thousands of kilometers above the atmosphere, is called Magnetosphere. Around this field our planet is exposed to the solar radiation known as ”solar winds”. These, in turn, according to their degree of intensity, can induce phenomena known as ”solar storms”, which can induce oscillations of voltage in electric power transmission lines and interference in satellite data communication. For the study and monitoring of the physical quantities related to these phenomena, besides the study of different types of rock formations and magnetic minerals, geologists and geophysicists from schools and universities around the world use equipment called magnetometers. In this context, this dissertation presents the EstGeoMag, a hardware-software solution of low-cost, based on concepts present in the Internet of Things, and which the main objective is to assist obtain geomagnetic quantities with high precision and accuracy. The proposed architecture is implemented using a Single Board Computer, Analogdigital converters, Fluxgate sensors, as well as software in C, Python, and Javascript. Several experiments and evaluations over the course of several months were performed as proof of concept, in order to demonstrate its feasibility, precision and accuracy when compared to commercial equipment.